The Poetics of the Crocodile: Changing Cultural Perspectives in Ambonwari. - Telban, Borut (Oceania, 2008)
Ambonwari people from the East Sepik Province, Papua New Guinea, had a rich repertoire of song-dances, each of which was associated with specific events and the birth of something new. Together they represented the entire human life cycle as well as the cosmology at large. Visual, verbal and tactile modalities of singing and dancing were tightly interwoven; images and symbols were enacted by the dancers, in their decoration, arrangement, movements and in the whole ceremony and were firmly situated in their landscape. Accordingly, song-dances were also an important practice in male initiation ritual. The first song-dance of the ritual was the crocodile song-dance. This article analyses different transpositions of images and meanings which can be decoded from the dance, from the objects that were part of the initiation rite, and from the parallelism and rich allegory of verses. These transpositions operate at different levels until they converge upon the existential facts of birth and death. In the new millennium and under the influence of a Catholic charismatic movement, however, Ambonwari broke off their relationships with spirits, abandoned the men's houses and stopped talking about male initiation ritual. Along with other traditional song-dances the crocodile song-dance has been taken over by the song-dances of the Holy Spirit. These changes in social and cultural perspectives, which are still taking place, are at the same time products and producers of the changes in their relationship to 'space' and 'time' which are at the same time changes in visual and auditory perception and expression of their life-world. All these changes should not be seen merely in some abstract or symbolic terms but as tangible processes generated by people's action.